Sustainable public food procurement: criteria and actors’ roles and influence - Molin, Elvira; Lingegård, Sofia; Martin, Michael; Björklund, Anna (Frontiers in Sustainable Food Systems, 2024)
Food production and consumption significantly contribute to climate change. The public sector, which procures large quantities of food, has a crucial role in steering toward more sustainable food systems. More empirical studies involving practitioners are called for to understand the complexity of sustainable public food procurement. This study examines how actors interpret and implement sustainability in food procurement, as well as their influence on this process. A comprehensive analysis of multi-actor collaboration and stakeholder engagement involving interviews with key actors such as procurement officers, wholesalers, chefs, and food producers is presented. Findings highlight a consensus on the need for sustainability measures, such as purchasing local and organic products. The results showcase the potential transformation of power dynamics within the supply chain in response to modifications in procurement standards toward local produce and the overuse of product-specific criteria. However, assuming that local is invariably sustainable carries the risk of falling into the “local trap” when the consequence of procuring local varies and requires further investigation. The influence of system-level factors, including market dynamics and regulatory frameworks, plays a significant role in implementing sustainable procurement, as well as alignment and coordination in the supply chain.